Oxa- and thia-fullerenes (C59O, C59S): Closed or opened cages? - Jiao, Haijun; Chen, Zhongfang; Hirsch, Andreas; Thiel, Walter (Physical Chemistry Chemical Physics, 2002)
Novel structures of oxa- and thia-fullerenes at various oxidation states have been computed systematically for the first time. At the B3LYP/6-31G* density functional level of theory, the most stable CO, CO CS represent cage opened structures with an eight-membered-ring orifice, bearing C=O or C=S moieties and two fused five-membered rings. On the other hand, CS, CS and CO are cage closed fullerenes. The calculated nucleus independent chemical shifts (NICS) of all these compounds are presented.